A Cyber Notary Based Notarial Deed Relating To The Obligation To Make An Authentic Deed - Meylita Dewi, Vania; Novy Purwanto, I Wayan (Dinasti Research, 2024)
The purpose of this research is to find out the regulations regarding cybernotaries in Indonesia and the validity of notarial deeds made through cyber notaries in relation to the obligation to make authentic deeds. This research uses a normative legal approach because of conflict norms, by analyzing legal concepts and legislative approaches, and using qualitative methods whose results are presented descriptively. Based on the analysis, it is known that regulations regarding cyber notaries in Indonesia are regulated in the UUJN. The validity of a cyber notary's notarial deed in issuing an authentic deed is considered valid if it complies with Article 16 paragraph (1) letter m and Article 38 UUJN and Article 1868 of the Civil Code.